Mythical Pictures of the South SlavsMitske podobe Južnih Slovanov - Čausidis, Nikos (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author writes about the so-called “mythical pictures”, a new source for the research of Slavic mythology, which were created in order to express people’s religious notions. The article is centered on four of the most common groups of mythical pictures which, due to their archetypal characteristics have survived to the present: paintings of the human body, those representing the female principle, solar mythical pictures, and the paintings of the male principle.